Load frequency control of microgrid - Zhao, Jianwei (2019)
Microgrids are becoming more and more important in the world’s energy portfolio. They can produce and distribute power in a campus setting or a small area. The balance between power generation and power demand is one of the most important requirements of microgrid management. In isolated operation mode, this grid can be considered as a weak electrical grid and a special attention must be paid for the frequency control due to the low inertia effect, since low inertia effect will cause the frequency deviation, and this deviation will cause machine tripping and blackout. In this project, the feedback frequency control are introduced to build the load frequency control system of microgrid and the battery energy storage system is introduced to improve the performance of the load frequency control.